2017
DOI: 10.1080/19932820.2017.1345582
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of complications of root canal treatment performed by undergraduate dental students

Abstract: This study evaluated the technical quality of root canal treatment (RCT) and detected iatrogenic errors in an undergraduate dental clinic at the College of Dentistry, Taibah University, Saudi Arabia. Dental records of 280 patients who received RCT between 2013 and 2016 undertaken by dental students were investigated by retrospective chart review. Root canal obturation was evaluated on the basis of the length of obturation being ≤2 mm from the radiographic apex, with uniform radiodensity and good adaptation to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
47
7
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(72 citation statements)
references
References 29 publications
10
47
7
3
Order By: Relevance
“…In this study sample, the overall quality of RCT was of 71.9%, which is higher than some studies reported [6,[16][17][18] and lower than others [10,19]. A systematic review recently published concluded that the frequency of acceptable RCTs performed by undergraduate students varies according to teeth groups [15].…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…In this study sample, the overall quality of RCT was of 71.9%, which is higher than some studies reported [6,[16][17][18] and lower than others [10,19]. A systematic review recently published concluded that the frequency of acceptable RCTs performed by undergraduate students varies according to teeth groups [15].…”
Section: Discussioncontrasting
confidence: 51%
“…In which, the only criteria grade as unacceptable was underfilling that was present in approximately 23%. Some authors described that with the increase in difficulty there is also a decrease in the quality of RCT performed by undergraduate students [3,16]. Root canal curvature may lead to challenges in instrumentation of all root canal length, which may lead to further complications in RCT, even for experienced professionals [4].…”
Section: Discussionmentioning
confidence: 99%
“…This was similar to some studies conducted by Kader et al 9 (50.7% for junior students and 69.3% for senior students) and Balto et al 13 (63.3% for the 4th year and 72.4% for the fifth year). It was comparatively superior to the other studies conducted by Alrahabi et al 14 Another factor investigated in the study was the density of obturation. Obturation with voids in between the filling and canal walls was considered as having inadequate density.…”
Section: Quality Of Obturation By Undergraduate Studentsmentioning
confidence: 59%
“…Acute pulpitis is prone to necrosis because the pulp is in a closed pulp chamber, lack of effective collateral circulation [1]. In clinic, pulp drying therapy, plasticization therapy and root canal therapy are effective methods to treat pulpitis, but both root canal therapy and other pulp therapy are at the cost of sacrificing part or whole of the pulps [2,3].…”
Section: Discussionmentioning
confidence: 99%